Strategi Optimasi Kinerja Teknologi Informasi Dalam Pengembangan Produk Baru pada Persaingan Pasar Dinamis - Harsanto; Afu Ichsan Pradana (CV. Doki Course and Training, 2025)
Abstract : The residential property construction industry in Indonesia faces dynamic challenges that demand strategic management of Information Technology (IT) performance. Limited resources and knowledge remain the main obstacles to IT optimization. This causal-comparative study examines the roles of IT performance optimization strategy, dynamic capability in new product development (NPD), functional competence, and market turbulence in achieving competitive advantage of new products. Analysis using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach reveals that dynamic capability and functional competence in NPD have a significant positive effect on competitive advantage, while IT optimization strategy and market turbulence show only weak positive effects. These findings emphasize the importance of strengthening internal competencies to develop adaptive business strategies in dynamic markets. Abstrak : Industri konstruksi properti residensial di Indonesia menghadapi tantangan dinamis yang menuntut strategi pengelolaan kinerja Teknologi Informasi (TI). Keterbatasan sumber daya dan pengetahuan menjadi kendala utama dalam optimasi TI. Penelitian kausal komparatif ini menguji peran strategi optimasi TI, kemampuan dinamis pengembangan produk baru (PPB), kompetensi fungsional, dan turbulensi pasar terhadap keunggulan kompetitif produk baru. Analisis menggunakan Structural Equation Modeling (SEM) berbasis Partial Least Squares (PLS) menunjukkan bahwa kemampuan dinamis PPB dan kompetensi fungsional berpengaruh signifikan terhadap keunggulan kompetitif, sementara strategi optimasi TI dan turbulensi pasar hanya memberikan pengaruh positif lemah. Hasil ini menegaskan pentingnya penguatan kompetensi internal untuk membangun strategi bisnis yang adaptif di pasar yang dinamis.